Human Immunoglobulin Versus Plasmapheresis in Guillain–Barre Syndrome and Myasthenia Gravis: A Meta-Analysis. Issue 1 (September 2016) - Ortiz-Salas, Paola; Velez-Van-Meerbeke, Alberto; Galvis-Gomez, Camilo Alberto; Rodriguez Q, Jesús H.
Abstract: Objectives: To evaluate the efficacy and safety over a short time period of human intravenous immunoglobulin versus plasma exchange (PE) in the management of some autoimmune neurologic diseases. In addition, length of hospital stay and duration of ventilator support were compared. Methods: Randomized controlled trials and analytical observational studies of more than 10 cases were reviewed. Cochrane Neuromuscular Disease Group trials, MEDLINE, EMBASE, HINARI, and Ovid, were searched as data source. Reference lists were examined for further relevant articles. A random-effect model was used to derive a pooled risk ratio. Results: A total of 552 articles were found and 24 met the criteria for a studied population of 4657 cases: 14 articles were about Guillain–Barré syndrome and 10 of myasthenia gravis. No evidence was found to suggest that PE or intravenous immunoglobulin differed in terms of efficacy or safety to treat any of the 2 diseases. Hospital stay length and ventilatory support time are different in each illness; however, we found no statistical difference in either of the 2 treatments. Conclusions: There is no evidence for superiority in the efficacy or safety of immunoglobulin or plasmapheresis in the management of Guillain–Barré syndrome and myasthenia gravis. However, caution should be exercised in the interpretation of these results given the limitations in the quality of the evidence and the heterogeneity of the studies. Abstract : Supplemental Digital Content is Available in the Text.